2016
DOI: 10.1002/2016gl070760
|View full text |Cite
|
Sign up to set email alerts
|

The Circumglobal North American wave pattern and its relation to cold events in eastern North America

Abstract: Extreme large‐scale North American cold events are associated with strong undulations in the tropospheric jet stream which bring cold polar air southward over the continent. Here we propose that these jet undulations are associated with the North American part of the Circumglobal Teleconnection Pattern—a pair of zonally oriented waves of zonal wave number 5 which are in zonal quadrature with each other. While the Pacific/North American pattern is associated with the first circumglobal wave pattern, North Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 41 publications
1
56
1
Order By: Relevance
“…The overall warming, which is to be expected from the increased amount of greenhouse gas loading in the atmosphere, contributed to the trend, but the spatially non‐uniform, somewhat wave‐like temperature trend pattern suggests that a large‐scale atmospheric Rossby wave train could have played an important role as well. In fact, the relevance of atmospheric Rossby waves in producing teleconnections that cause extreme heatwaves has long been recognized (Trenberth and Branstator, ; Lyon and Dole, ; Dole et al ., ; Lau and Kim, ; Petoukhov et al ., ; Teng et al ., ; Coumou et al ., ; Harnik et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The overall warming, which is to be expected from the increased amount of greenhouse gas loading in the atmosphere, contributed to the trend, but the spatially non‐uniform, somewhat wave‐like temperature trend pattern suggests that a large‐scale atmospheric Rossby wave train could have played an important role as well. In fact, the relevance of atmospheric Rossby waves in producing teleconnections that cause extreme heatwaves has long been recognized (Trenberth and Branstator, ; Lyon and Dole, ; Dole et al ., ; Lau and Kim, ; Petoukhov et al ., ; Teng et al ., ; Coumou et al ., ; Harnik et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Prior to plotting, two iterations of nine-point local smoothing were performed on (a) and the zonal mean was removed from (b). Stippling indicates statistical significance at the 95% confidence level, as derived from a Monte Carlo simulation with 1,000 random samples 1992; Lyon and Dole, 1995;Dole et al, 2011;Lau and Kim, 2012;Petoukhov et al, 2013;Teng et al, 2013;Coumou et al, 2014;Harnik et al, 2016).…”
mentioning
confidence: 99%
“…Pinto et al, 2013;van Oldenborgh et al, 2015;Huntingford et al, 2014;Wild et al, 2015) and cold spells in North America (e.g. Trenary et al, 2015;Lee et al, 2015;Messori et al, 2016;Harnik et al, 2016) have attracted in recent years. The analysis in Section 5.1 primarily aims to relate the information provided by our metrics to known features of the atmospheric variability over the Euro-Atlantic region, and can be viewed as a test of the robustness of the metrics we propose.…”
Section: Introductionmentioning
confidence: 99%
“…Baxter and Nigam (2015) demonstrated that, during the winter of 2013/2014, the North Pacific Oscillation-WP teleconnection provided a major contribution to the North American circulation anomaly. Harnik et al (2016) discovered that a large number of extreme North American cold events are related to jet stream undulations similar to the circumglobal North America pattern (Branstator 2002). Although the statistical significance between planetary climate modes and seasonal ECW behavior is well established, little information exists regarding the intraseasonal links between planetary climate modes and ECWs or the underlying physics behind these relationships.…”
Section: Introductionmentioning
confidence: 99%